Pengaruh Tepung Daun Sirsak (Announa Muricata L) terhadap Karakteristik Lemak Darah dan Daging Itik Tegal Jantan - Elly Tugiyanti; Soegeng Heriyanto; Afduha Nurus Syamsi (Buletin Peternakan, 2016)
The purpose of this experiment was to evaluate the effect of soursop leaf meal on characteristics of  blood and meat  fat of male Tegal ducks. This study used completely randomized design. The study consisted of four treatments, namely: feed without supplementation of soursop leaf meal, feed with 5% soursop leaf meal, feed with 10% soursop leaves meal, and feed with 15% soursop leaf meal. Each treatment was 5 replications and each replication consisted of five ducks. The treatment given to duck for 5 weeks started from 4 to 10 weeks of age. Data were analyzed by Analysis of Variance (ANOVA) continued by orthogonal polynomial test. The results showed that soursop leaf meal supplementation in feed had no significant effect on levels of blood triglycerides, cholesterol, and LDL as well as meat triglycerides and cholesterol, but it affected levels of HDL significant (P<0.01), ie increase HDL levels. It can be concluded that soursop leaf meal supplementation in male Tegal duck feed by 8.36% showed the highest blood HDL levels (99.89 mg/dl), however soursop leaf meal supplementation up to 15% did not affect levels of blood triglycerides, cholesterol, and LDL as well as levels of meat triglycerides and cholesterol of 9 weeks male tegal duck.